Power quality, smart meters and additional information from different power terms - Souza, W. A.; Marafão, F. P. [UNESP]; Liberado, E. V.; Diniz, I. S. [UNESP]; Serni, P. J.A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
This paper shows how the detailed examination of active and nonactive power components may produce new information for modern smart meters. For this purpose, a prototype of electronic power meter has been implemented and applied to the evaluation of the Conservative Power Theory (CPT). Considering five sorts of loads, under four different operating conditions, the experimental results indicate that the CPT is able to provide a good methodology for load characterization, which could possibly benefits consumers and power utilities in several different ways. The results also show that depending on the situation, the analysis of nonactive power terms may be more important than the observation of traditional power quality indices, such as total harmonic distortion, unbalance factors or the fundamental positive sequence power factor.
Keywords: Conservative Power Theory; Power Meters; Power Quality; Revenue Metering; Smart Grids; Smart meters